Low dose radiotherapy is associated with local complications but not disease control in sacral chordoma. Issue 7 (7th February 2019) - Houdek, Matthew T.; Rose, Peter S.; Hevesi, Mario; Schwab, Joseph H.; Griffin, Anthony M.; Healey, John H.; Petersen, Ivy A.; DeLaney, Thomas F.; Chung, Peter W.; Yaszemski, Michael J.; Wunder, Jay S.; Hornicek, Francis J.; et al.
Abstract: Background: We reviewed the disease control and complications of the treatment of sacrococcygeal chordoma from four tertiary cancer centers with emphasis on the effects of radiotherapy in surgically treated patients. Methods: A total of 193 patients with primary sacrococcygeal chordoma from 1990 to 2015 were reviewed. There were 124 males, with a mean age of 59 ± 15 years and a mean follow‐up of 7 ± 4 years. Eighty‐nine patients received radiotherapy with a mean total dose of 61.8 ± 10.9 Gy. Results: The 10‐year disease‐free and disease‐specific survival was 58% and 72%, respectively. Radiation was not associated with local recurrence (hazard ratio [HR], 1.13; 95% confidence interval [CI], 0.59‐2.17; P  = 0.71), metastases (HR, 0.93; 95% CI, 0.45‐1.91; P  = 0.85) or disease‐specific survival (HR, 0.96; 95% CI, 0.46‐2.00; P  = 0.91). Higher doses (≥70 Gy; HR, 0.52; 95% CI, 0.20‐1.32; P  = 0.17) may be associated with reduced local recurrence. Radiotherapy was associated with wound complications (HR, 2.76; 95% CI, 1.64‐4.82;, P  < 0.001) and sacral stress fractures (HR, 4.73; 95% CI, 1.88‐14.38; P  < 0.001). Conclusions: In this multicenter review, radiotherapy was not associated with tumor outcome but associated with complications. The routine use of radiotherapy with en‐bloc resection of sacrococcygeal chordomas should be reconsidered in favor of a selective, individualized approach with a radiation dose of ≥70 Gy.